Assosiation between The Level of Osteoporosis Knowledge with Behavior of Consuming Milk among Students of Class XI SMA N 1 Surakarta - Sari, Aprilisasi Purnama; ., Suhanantyo; Hidayati, Rosalia Sri (Nexus Kedokteran Komunitas, 2015)
Background: The increasing life expectancy of Indonesian society leads to health problems such as degenerative diseases, one of them is osteoporosis. The Health Department of Indonesia declare that two of five Indonesian people are at risk of osteoporosis so possessing the osteoporosis knowledge and its preventive effort are needed. As preventive, milk which is one of calcium sources can be adequately consumed to attain optimal peak bone mass on adolescence. This study aimed to find out whether there is association between the level of osteoporosis knowledge with behavior of consuming milk among students of class XI SMA N 1 Surakarta. Methods: This analytical observational research used cross sectional approach. It was carried out at SMA N 1 Surakarta on September 11th and 25th 2014. Dependent variable is the level of osteoporosis knowledge, while independent variable is behavior of consuming milk. Samples taken by total sampling and using inclusion criteria and exclusion criteria. Sample size was 228 according to the number of students of class XI whom fulfill all the inclusion criteria and none of the exclusion criteria. Data was collected from the questionnaires filled by respondents. Questionnaires then be scored, grouped into appropriate category and then analyzed using Chi Square test. Results: From 228 students, it is found that 24 (10,53%) students have good level of osteoporosis knowledge, 162 (71,05%) students have enough level of osteoporosis knowledge and 42 (18,42%) students have less level of osteoporosis knowledge. The number of students who have adequate behavior of consuming milk for each level of osteoporosis knowledge, respectively is 6 students, 26 students and 7 students. There is no association between the level of osteoporosis knowledge with behavior of consuming milk of students of class XI SMA N 1 Surakarta showed by the score p = 0.661 (p > 0.05) as results of Chi Square statistical calculation Conclusions: There is no assosiation between the level of osteoporosis knowledge with behavior of consuming milk among students of class XI SMA N 1 Surakarta. Keywords: level of osteoporosis knowledge, behavior of consuming milk Â  Â